Impact of Nox5 Polymorphisms on Basal and Stimulus-Dependent ROS Generation - Wang, Yusi (Public Library of Science, 2014)
Nox5 is an EF-hand containing, calcium-dependent isoform of the NADPH oxidase family of reactive oxygen species (ROS) generating enzymes. Altered expression and activity of Nox5 has been reported in cardiovascular diseases and cancers but the absence of Nox5 in rodents has precluded a greater understanding of its physiological and pathophysiological roles. Multiple polymorphisms have been identified within the coding sequence of human Nox5, but whether this translates into altered enzyme function is unknown. Herein, we have generated 15 novel mutants of Nox5β to evaluate the effect of exonic SNPs on basal and stimulated enzyme activity. Compared to the WT enzyme, ROS production was unchanged or slightly modified in the majority of mutants, but significantly decreased in 7. Focusing on M77K, Nox5 activity was dramatically reduced in unstimulated cells and following challenge with both calcium- and phosphorylation-dependent stimuli despite equivalent levels of expression. The M77K mutation did not influence the Nox5 phosphorylation or the ability to bind Hsp90, but in cell-free assays with excess co-factors and calcium, ROS production was dramatically reduced. A more conservative substitution M77V arising from another SNP yielded a different profile of enzyme activity and suggests a critical role of M77 in calcium-dependent ROS production. Two C-terminal mutants, R530H and G542R, were observed that had little to no activity and relatively high minor allele frequency (MAF). In conclusion, we have identified 7 missense SNPs in Nox5 that result in little or no enzyme activity. Whether humans with dysfunctional Nox5 variants have altered physiology or disease remains to be determined.